Which species of the genus Scaurus Fabricius (Coleoptera: Tenebrionidae) occurs in the Caucasus and the border areas of Anatolia?. Issue 2 (3rd April 2018) - Nabozhenko, Maxim; Kovalenko, Yakov; Kalashian, Mark
Abstract : A redescription of the male of Scaurus araxinus Richter, 1945 is given and the female is described for the first time. The species occurs in Azerbaijan (Nakhichevan Republic), Armenia (Tigranashen and Yeghegnadzor) and Eastern Turkey (first record in Iğdır province). It had been regarded as conspecific with S. syriacus Reitter, 1914 and S. puncticollis Solier, 1838 but clearly differs from both these species and is close to S. rugicollis Reitter, 1914 from the Mediterranean region. The female genital tubes of S. araxinus are figured, the first such illustration for the tribe Scaurini. The genus Scaurus has a small secondary bursa copulatrix, separated glandular, moderately short, spermatheca and a relatively short accessory gland, similar to those found in some genera of the tribe Helopini.